Photoshop CS6 : the missing manual - Snider, Lesa (Missing manual., 2012)
Photoshop CS6 is truly amazing, but it can also be overwhelming if you're just getting started. This book makes learning Photoshop a breeze by explaining things in a friendly, conversational style--without technical jargon. After a thorough introduction to the program, you'll delve deep into Photoshop's secrets with expert tips and practical advice you can use every day. The important stuff you need to know: Learn your way around. Get a guided tour of Photoshop's beautiful new workspace. Unlock the magic. Discover the most practical ways to use layers, channels, masks, paths, and other tools. Fine-tune your images. Learn techniques for cropping, retouching, and combining photos. Play with color. Drain, change, and add color; and create gorgeous black-and-whites and duotones. Be artistic. Create original illustrations and paintings, use text and filters effectively, and edit video clips. Share your work. Produce great-looking images for print and the Web. Work smarter and faster. Automate common chores and install plug-ins for complex tasks.